Transfer Pricing: A Behavioral Context. - Watson, David J. H.; Baumler, John V. (The Accounting Review, 1975)
This article presents a behavioral approach to transfer pricing problems. Since the transfer pricing problem only arises within a recognizable social system, be it an organization or a socialist economy, this article considers the solutions in a social system context. The paradigm developed can then be used to evaluate the usefulness and limitations of the various proposed solutions. Decentralization is one approach to organizational design. Implicit in this approach is the segmentation of the organization into various specialities. Numerous reasons are provided in the transfer price literature for decentralization. Decentralization, however, does not quite explain the process involved. A consequence of the segmentation of the organization into parts is that the behavior of organizational members will be influenced by the segmentation. Therefore, the term "differentiation" is used to include not only the segmentation of the organization into specialized parts, but also to include the consequent differences in attitudes and behavior of organizational members.